Quality of Management Education: An Indian Perspective - Kalla, Neelam (Scholar: Human Sciences, 2014)
In past few years, India has emerged as one of the fastest growing educational hubs of the globe. Earlier, known as cultural nation, now India is called a land of culture and education. In the process of providing educational services, various professional courses, abbreviating gender disparities and promoting education, the educational face of the nation has been changing frequently. In this transformation the growth of management education has excelled all other fields, at present in India there is a good number of mushrooming management institutes is also there to provide degrees or diplomas, and not very surprisingly the result of this entire network of such educational institutes is creation of a pool of MBAs who are qualified degree holders but their contribution in society and economy is not very outstanding. The concerns about the relevance of management course content in Indian context, need for restructuring the completely Indian management education system to inculcate larger relevance with developing Indian economy and to provide all resources to create a vibrant and rigorous academic community of management scientist have dominated the scenario in past few years.